مساهمة الجامعة في دعم ونمو المؤسسات الناشئة في الجزائر - غمام جريدي الهادي (جامعة الوادي University of Eloued, 2024)
الهدف من هذه الدراسة هو إبراز دور الجامعات في تعزيز ونمو المؤسسات الناشئة في الجزائر،حيث يعتبر دعم المؤسسات الناشئة أحد المحركات الرئيسية للتنمية الاقتصادية وتعزيز الابتكار وخلق فرص العمل. يتناول المقال عدة جوانب من خلال استعراض السياسات والمبادرات الجامعية التي تدعم ريادة الأعمال، والدعم المالي والفني، والتوجيه والمشورة، وثقافة ريادة الأعمال. وتم استخدام المنهج الوصفي ، وتوصلت الدراسة إلى أن الجامعات تلعب دورا هاما في دعم المؤسسات الناشئة من خلال توفير المعرفة والمهارات الضرورية والدعم المالي والفني. و من أهم التوصيات: تعزيز البنية التحتية واعتماد التقنيات الحديثة في الجامعات لدعم الابتكار والريادة، و تطوير برامج تعليمية مخصصة لريادة الأعمال وتوفير المزيد من التمويل والدعم الفني للشركات الناشئة وتعزيز التعاون بين القطاعين العام والخاص. The objective of this study is to highlight the role of universities in the promotion and growth of startups in Algeria and study initiatives and programs offered by universities to help start-ups develop and instill the spirit of innovation by providing emerging entrepreneurs with knowledge, skills, finance, mentoring and supporting infrastructure through incubators and entrepreneurial centers, Universities have contributed to the emergence of an ecosystem supportive of the growth of Algeria's startups and its ability to expand into competitive markets, and a powerful driver of innovation and economic development While its role is important, it faces several challenges that impede universities' ability to support and grow start-ups, most notably limited financing and bureaucratic constraints.
The University's contribution to the support and growth of startups in Algeria
Keywords: مؤسسات ناشئة; الجامعة; حاضنات الأعمال الجامعية; الجزائر; startups; university; university business incubators; Algeria